A 266-nm multi-reflection laser curtain for airborne bacterial inactivation in a 20-m3 chamber and a single-pass duct testbed - Chenjie Guo (Frontiers in Public Health, 2026)
Background Airborne transmission remains a challenge for infection prevention and control in healthcare environments, motivating compact air-disinfection technologies. Methods A compact 266 nm multi-reflection laser-curtain module was developed, providing two effective curtain widths (96 mm and 200 mm). Aerosolised Staphylococcus albus (S. albus; a coagulase-negative staphylococcal bacterial surrogate) was tested in (i) a mixed-air 20 m 3 enclosure for time-dependent inactivation and (ii) a duct-flow single-pass rig using three curtains in series with paired upstream-downstream sampling. Matched no-UV controls were used for baseline correction, with first-order kinetics used for room-scale analysis. Results In the 20 m 3 enclosure, inactivation increased with operating time. The 96 mm curtain achieved ~66–69% at 5 min and exceeded 98% by 30 min, approaching ≥99.9% with extended operation. The 200 mm curtain exceeded 99.5% by 20 min and approached ≥99.99% at longer times, with a numerically higher apparent rate constant (0.190 vs. 0.127 min −1 ). In the duct-flow system, three curtains maintained ≥99.0% single-pass inactivation across 1.2–9.6 m/s. Conclusions The multi-reflection 266 nm laser-curtain achieved high inactivation in controlled room-scale and duct single-pass tests, supporting further engineering evaluation of this air-disinfection concept rather than immediate healthcare deployment.